Can species‐specific prey responses to chemical cues explain prey susceptibility to predation?. Issue 9 (10th April 2018) - Šmejkal, Marek; Ricard, Daniel; Sajdlová, Zuzana; Čech, Martin; Vejřík, Lukáš; Blabolil, Petr; Vejříková, Ivana; Prchalová, Marie; Vašek, Mojmír; Souza, Allan T.; Brönmark, Christer; Peterka, Jiří
Abstract: The perception of danger represents an essential ability of prey for gaining an informational advantage over their natural enemies. Especially in complex environments or at night, animals strongly rely on chemoreception to avoid predators. The ability to recognize danger by chemical cues and subsequent adaptive responses to predation threats should generally increase prey survival. Recent findings suggest that European catfish ( Silurus glanis ) introduction induce changes in fish community and we tested whether the direction of change can be attributed to differences in chemical cue perception. We tested behavioral response to chemical cues using three species of freshwater fish common in European water: rudd ( Scardinius erythrophthalmus ), roach ( Rutilus rutilus ), and perch ( Perca fluviatilis ). Further, we conducted a prey selectivity experiment to evaluate the prey preferences of the European catfish. Roach exhibited the strongest reaction to chemical cues, rudd decreased use of refuge and perch did not alter any behavior in the experiment. These findings suggest that chemical cue perception might be behind community data change and we encourage collecting more community data of tested prey species before and after European catfish introduction to test the hypothesis. We conclude that used prey species can be used as a model species to verify whether chemical cue perception enhances prey survival. Abstract : Especially in complex environments or at night, animals strongly rely on chemoreception to avoid predators. The ability to recognize danger by chemical cues and subsequent adaptive responses to predation threats should generally increase prey survival. We compared three prey species ability to sense the danger and reviewed their susceptibility to predation.